How to Increase Strategic Supply Chain Resilience in 5 Steps - Obrecht, Matevž (Strategije in pristopi večanja odpornosti in prožnosti oskrbovalnih verig, 2025)
Recognizing that the reliability of the supply on the global market has been risky for some time has become an undeniable fac in times of disruptions. Big international supply chain players have been dealing with this issues for over a decade. If we want our supply chain to be resilient, we must be aware that to enhance resilience, we need to forecast potential disruptions and develop scenarios how to manage them. For flexible and resilient supply chain it is crucial to have clearly defined supply chain strategy based on a) Risk analysis; b) Value chain analysis and c) Maturity model and benchmarking. This helps us to identify priority measures and to develop an action plan to achieve greater resilience and adaptability, which are becoming foundation of business in the 5.0 society.